Analysis and application of an outsourcing risk framework - Abdullah, Lili Marziana; Verner, June M. (Elsevier, 2012)
There is much reported research on risk, and risk management but research on strategic IT system development outsourcing risk, from the client perspective, remains unclear. A literature-based conceptual risk framework for strategic IT system development outsourcing from the client perspective has been developed. We then investigate, (1) critical client risks for strategic IT system development outsourcing projects, and (2) the most common critical client risk factors for such projects. In order to identify any serious omissions in our framework an initial validation of the risk framework is provided through a review of nine published cases of unsuccessful strategic IT system development outsourcing projects. The risks critical to a client are associated with complexity, contract, execution, financial, legal, the organizational environment, planning and control, scope and requirements, the team, and the user. Risks manifest in all nine published cases, include (1) complexity and (2) the team. Three risk factors not previously identified in the initial framework are included in a revised framework. The risk framework assisted us in identifying a number of critical risk factors affecting the outcome of strategic IT system development outsourcing projects.